An Analysis of Students in Independent Learning of Analytic Geometry During the COVID-19 Pandemic - Bilda, Westi; Fadillah, Ahmad (JTAM (Jurnal Teori dan Aplikasi Matematika), 2020)
The purpose of this study is to analyse the independence of students learning on the flat analytic geometry of the Covid-19. This research was conducted on students in the second semester with 72 resopondents consisting of 15 males and 52 females. Data retrieval is carried out using a self-sufficiency study poll as many as 20 items of statements that have been compiled based on learning independence indicators. The scale used in this study was the Likert scale. Data analysis to know the independence of learning students used descriptive analytical techniques with the ideal criteria namely the ideal mean and the ideal deviation standard. Based on data analysis obtained by the results of independence of learning with indicators: a self- confident is good enough (31.75%), the activeness is quite good (37.50%), discipline is good (52.10%), and responsibility is good (64.57%).